2016
DOI: 10.1016/j.jiph.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of occult hepatitis B virus infection in Egyptian hemodialysis patients without hepatitis C virus infection

Abstract: OBI is likely among hemodialysis patients even without HCV coinfection (24%). Genotype D cannot be the only genotype distributed in Upper Egypt, as the current study reported relatively new results that 50% of the patients with occult B carry genotype B, 33.3% carry genotype C and only 16.6% carry genotype D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…In contrast, genotypes B and C were initially identified in other regions of the world, such as Asia, Australia, Greenland, and Canada[ 35 ]. However, they have been found in Africa as well, specifically in Egypt[ 40 - 43 ] and Ethiopia[ 44 ]. The geographic distribution of HBV genotypes is associated with distinct modes of HBV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, genotypes B and C were initially identified in other regions of the world, such as Asia, Australia, Greenland, and Canada[ 35 ]. However, they have been found in Africa as well, specifically in Egypt[ 40 - 43 ] and Ethiopia[ 44 ]. The geographic distribution of HBV genotypes is associated with distinct modes of HBV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of reports (7/10) reported that genotype D predominated. However, Esmail et al, Zaki et al, and Elmaghloub et al, reported that genotypes B, E, and C were the most prevalent, [ 20 , 21 , 64 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…High frequencies of OBI have been detected among different high-risk populations in Egypt, including blood donors, and patients with chronic hepatitis C, haemodialysis, polytransfusion and haematological and solid malignancies (9). HBV genotypes B-D have been detected among Egyptian OBI patients (9,10). In this study we aimed to clarify the overall prevalence of OBI among Egyptian HCWs.…”
Section: ‫مرص‬ ‫يف‬ ‫الصحية‬ ‫الرعاية‬ ‫جمال‬ ‫يف‬ ‫العاملني‬ ‫بني‬ ‫mentioning
confidence: 99%